(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores how mathematical training, particularly in algebra, can foster intuitive competence in military cadets. Intuitive competence – the ability to make quick, informed decisions and perceive patterns instinctively – is a crucial skill for future officers. We argue that mathematics education sharpens cadets’ cognitive abilities, enabling them to educate their intuition through structured problem-solving experiences. The paper discusses why intuition matters in military contexts, how algebraic thinking builds mental frameworks for rapid decision-making, and provides a real-life example of a cadet using algebra to enhance intuitive judgement in a tactical scenario.